A detailed investigation of low latitude tweek atmospherics observed by the WHU ELF/VLF receiver: I. Automatic detection and analysis method. Issue 2 (30th March 2020) - Zhou, RuoXian; Gu, XuDong; Yang, KeXin; Li, GuangSheng; Ni, BinBin; Yi, Juan; Chen, Long; Zhao, FuTai; Zhao, ZhengYu; Wang, Qi; Zhou, LiQing
Abstract : As a dispersive wave mode produced by lightning strokes, tweek atmospherics provide important hints of lower ionospheric (i.e., D‐region) electron density. Based on data accumulation from the WHU ELF/VLF receiver system, we develop an automatic detection module in terms of the maximum‐entropy‐spectral‐estimation (MESE) method to identify unambiguous instances of low latitude tweeks. We justify the feasibility of our procedure through a detailed analysis of the data observed at the Suizhou Station (31.57°N, 113.32°E) on 17 February 2016. A total of 3961 tweeks were registered by visual inspection; the automatic detection method captured 4342 tweeks, of which 3361 were correct ones, producing a correctness percentage of 77.4% (= 3361/4342) and a false alarm rate of 22.6% (= 981/4342). A Short‐Time Fourier Transformation (STFT) was also applied to trace the power spectral profiles of identified tweeks and to evaluate the tweek propagation distance. It is found that the fitting accuracy of the frequency–time curve and the relative difference of propagation distance between the two methods through the slope and through the intercept can be used to further improve the accuracy of automatic tweek identification. We suggest that our automatic tweek detection and analysis method therefore supplies a valuable means to investigate features of low latitude tweek atmospherics and associated ionospheric parameters comprehensively.